Implementation of H5P-assisted Teaching Materials on Mathematical Understanding Based on Learning Style - Arif Abdul Haqq; Hendri Handoko; Anita Syafianti (EduMa: Mathematics education learning and teaching, 2024)
This study aimed to examine the impact of H5P-assisted teaching materials on students' mathematical understanding, with a focus on the role of learning styles. Utilizing a quasi-experimental design with a pretest-posttest control group model, the research was conducted among students from two homogeneous classes within the Mathematics Education Program at UIN Siber Syekh Nurjati Cirebon. The participants consisted of 99 students selected through purposive sampling based on their initial mathematical abilities to ensure comparability between groups. These participants were then divided into an experimental group, which utilized H5P interactive teaching materials, and a control group, which received conventional instruction. The findings indicated that students with a visual learning style exhibited significantly greater enhancements in mathematical understanding compared to those with auditory and kinesthetic learning styles after exposure to H5P-assisted materials. ANOVA and multiple comparison (LSD) tests revealed significant differences between the visual group and both the auditory and kinesthetic groups, with no significant differences between the latter two groups. These results highlight the importance of tailoring teaching materials to students' learning styles to enhance mathematics learning outcomes